2021
DOI: 10.3892/or.2021.7935
|View full text |Cite
|
Sign up to set email alerts
|

Role of ERCC5 polymorphisms in non‑small cell lung cancer risk and responsiveness/toxicity to cisplatin‑based chemotherapy in the Chinese population

Abstract: Non-small cell lung cancer (NSCLC) is the leading cause of cancer-related deaths worldwide. Cisplatin-based chemotherapy currently represents the main treatment option for patients with NSCLC. The aim of the present study was to evaluate effect of single nucleotide polymorphisms (SNPs) within the excision repair cross-complementing group 5 (ERCC5) gene on susceptibility to NSCLC, as well as the responsiveness to and toxicity of cisplatin chemotherapy. A total of 506 patients with NSCLC and 510 healthy controls… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Metaanalysis results showed that pembrolizumab combined with chemotherapy improved 1-year survival rate and prolonged OS, with statistically significant differences compared with chemotherapy alone, while complete response rate, PFS, and chemotherapy alone showed no statistically significant differences. Relevant studies [36][37][38] also showed that pembrolizumab combined with chemotherapy had a higher proportion of grade 3 and 4 leukopenia, rash, and infusion reaction than chemotherapy alone, and the difference was statistically significant, but there was no increase in the mortality rate. Therefore, pembrolizumab is effective and safe.…”
Section: Discussionmentioning
confidence: 99%
“…Metaanalysis results showed that pembrolizumab combined with chemotherapy improved 1-year survival rate and prolonged OS, with statistically significant differences compared with chemotherapy alone, while complete response rate, PFS, and chemotherapy alone showed no statistically significant differences. Relevant studies [36][37][38] also showed that pembrolizumab combined with chemotherapy had a higher proportion of grade 3 and 4 leukopenia, rash, and infusion reaction than chemotherapy alone, and the difference was statistically significant, but there was no increase in the mortality rate. Therefore, pembrolizumab is effective and safe.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study demonstrated that ERCC5 (key components of the nucleotide excision repair pathway) was remarkably associated with susceptibility to tumors[ 31 ]. Li et al reported that ERCC5 was significantly associated with the response of cisplatinbased chemotherapy of non-small cell lung cancer[ 32 ]. Another study reported that the expression level of ERCC5 was significantly increased in hepatocellular carcinoma, and high ERCC5 expression conferred poor prognosis[ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other than KRAS, most of the smokingassociated mutations comprise loss-of-function of tumorsuppressive deoxyribonucleic acid (DNA)-damage repair genes, such as excision repair complementary complex 5 and 8 (ERCC5, ERCC8), DNA ligase 4 (LIG4), mutY DNA glycosylase (MUTYH), DNA polymerase beta (POLB), DNA repair protein REV1 as well as G/T mismatchspecific thymine DNA glycosylase (TDG) (9). While some of these genetic aberrations might predict responsiveness to platinum-based chemotherapies (13)(14)(15)(16), none of them have been translated into targeted NSCLC therapies yet. Thus, discovery of novel targets for the treatment of smokingrelated lung cancer is of primary importance.…”
Section: Introductionmentioning
confidence: 99%